1989
DOI: 10.1128/aac.33.8.1188
|View full text |Cite
|
Sign up to set email alerts
|

Cefotiam disposition in markedly obese athlete patients, Japanese sumo wrestlers

Abstract: Markedly obese athletes like Japanese sumo wrestlers may frequently suffer various traumas which result in the prophylaxis or treatment of posttraumatic infection with antibiotics. However, appropriate dosage regimens in this group of patients have not been fully known for many antibiotics. Therefore, we studied the kinetic disposition of cefotiam, a parenteral, broad-spectrum cephalosporin with activity against gram-positive and -negative bacteria, after an intravenous dose (2 g) infused over 30 min into 15 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…The effect of altered body composition on drug disposition and therapeutic outcome with increasing obesity is particularly pertinent in antimicrobial therapy. Suboptimal drug exposure can lead to clinical failure and increase the risk of drug resistance.Several studies that specifically examined drug disposition of ␤-lactam antibiotics in obesity found an increase in the volume of distribution and/or drug clearance in obese subjects (3,12,24). This suggests that such patients may require higher doses or more frequent administration in order to achieve adequate drug exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of altered body composition on drug disposition and therapeutic outcome with increasing obesity is particularly pertinent in antimicrobial therapy. Suboptimal drug exposure can lead to clinical failure and increase the risk of drug resistance.Several studies that specifically examined drug disposition of ␤-lactam antibiotics in obesity found an increase in the volume of distribution and/or drug clearance in obese subjects (3,12,24). This suggests that such patients may require higher doses or more frequent administration in order to achieve adequate drug exposure.…”
mentioning
confidence: 99%
“…Several studies that specifically examined drug disposition of ␤-lactam antibiotics in obesity found an increase in the volume of distribution and/or drug clearance in obese subjects (3,12,24). This suggests that such patients may require higher doses or more frequent administration in order to achieve adequate drug exposure.…”
mentioning
confidence: 99%
“…This phenomenon is magnified for lipophilic medications, which tend to more readily distribute than hydrophilic drugs. Previous work has identified larger V d in obese patients for most classes of antimicrobial agents, including penicillins, cephalosporins, carbapenems, aminoglycosides, vancomycin, and others [16][17][18][19][20][21][22][23][24][25]. The extent to which a medication is protein-bound also affects V d , and obesity has been shown to alter lipoproteins and alpha1-acid glycoprotein [2].…”
Section: Discussionmentioning
confidence: 99%
“…Studien für den Einsatz von Cephalosporinen zeigen, dass bei Adipositas die Clearance und das Verteilungsvolumen der Cephalosporine vergrößert sind. Hieraus ergibt sich die Notwendigkeit einer Dosisanpassung beim Einsatz von Cephalosporinen, insbesondere als Single-Shot-Prophylaxe [14,15]. Auch für Betalaktam-Antibiotika wurde dieser Effekt nachgewiesen [16].…”
Section: Anforderungen An Die Perioperative Antibiotikatherapieunclassified